Kindlin-3–independent adhesion of neutrophils from patients with leukocyte adhesion deficiency type III - van de Vijver, Edith; Tool, Anton T.J.; Sanal, Özden; Çetin, Mualla; Ünal, Sule; Aytac, Selin; Seeger, Karl; Pagliara, Daria; Rutella, Sergio; van den Berg, Timo K.; Kuijpers, Taco W. (Journal of allergy and clinical immunology, 2014)
Activation of hematopoietic integrins to a high-affinity ligand-binding conformation requires interaction with several cytoplasmic proteins, including kindlin-3.2 The importance of kindlin-3 is illustrated by leukocyte adhesion deficiency type III (LAD-III), a rare autosomal-recessive syndrome caused by mutations in FERMT3, the gene encoding kindlin-3.3 LAD-III manifests with recurrent nonpurulent bacterial and fungal infections as well as with a Glanzmann thrombasthenia-like bleeding tendency, caused by normal expression but defective activation of integrins on leukocytes and platelets.4 Although the relevance of kindlin-3 is no longer disputed, it is still unclear how and when it contributes to the activation of the Î²2 integrins. Adhesion of LAD-III neutrophils was strongly decreased when induced with Toll-like receptor (TLR) ligands Pam3Cys and lipopolysaccharide-binding protein/lipopolysaccharide or with G-protein-coupled receptor (GPCR) ligands platelet-activation factor and C5a.